Solusi Konflik Rasial pada Masyarakat Multikultural dalam Perspektif Al-Qur’an - Abdul Muid Nawawi; Mulawarman Hannase; Iwan Satiri (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
Conflicts that still often occur in multicultural communities such as in Indonesia is racial conflict. Racial conflicts in Indonesia have occurred between Batak ethnic groups and Flores on July 12, 1999 on Batam; between indigenous and ethnic Chinese on January 4, 2000 in Pekalongan, Central Java; and between the Madurese tribe and the Dayak tribe on February 18, 2001 in Sampit Borneo. According to Sayyid Qutb the Qur’an describes a solution in the form of preventive measures so that things that can cause potential conflicts, such as prohibiting insulting, prohibiting gossiping, and prejudice prohibitions. This paper tries to offer a preventive and persuasive solution to racial conflict in the perspective of the Qur’an